2012
DOI: 10.6064/2012/158646
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging and Neurocognitive Correlates of Aggression and Violence in Schizophrenia

Abstract: Individuals diagnosed with major mental disorders such as schizophrenia are more likely to have engaged in violent behavior than mentally healthy members of the same communities. Although aggressive acts can have numerous causes, research about the underlying neurobiology of violence and aggression in schizophrenia can lead to a better understanding of the heterogeneous nature of that behavior and can assist in developing new treatment strategies. The purpose of this paper is to review the recent literature an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 137 publications
1
25
0
Order By: Relevance
“…This is consistent with evidence that abnormalities in fronto-temporal circuitry are implicated in aggressive behavior among such patients (Weiss, 2012).…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with evidence that abnormalities in fronto-temporal circuitry are implicated in aggressive behavior among such patients (Weiss, 2012).…”
Section: Introductionsupporting
confidence: 91%
“…Data exploring the link between executive deficits and risk of violence in schizophrenia are inconsistent (Weiss et al, 2012;Witt et al, 2013). Current psychopathology, social reasoning and functioning have also been reported to be linked to violence (Serper et al, 2008;O'Reilly et al, 2015), though a recent meta-analysis found that only global cognitive impairment and lack of insight predicted violence in schizophrenia (Reinharth et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The link between gelotophobia with anger and aggression proneness may in part be explained by its association with poor emotion regulation capacities. Basic processes contributing to heightened levels of trait anger and aggression in the general population as well as in psychiatric patients (Weiss, 2012;Wilkowski & Robinson, 2010) include the tendency to attribute hostile traits to other persons (see also Dodge, 1993;McNiel, Eisner, & Binder, 2003;Weiss et al, 2006), which may be in line with the disposition of individuals with gelotophobia to assume that laughter in their presence is directed at them and thus hostile, and poor regulation of angry thoughts and feelings (see also Davidson, Putnam, & Larson, 2000). Previous research has demonstrated that, compared to nongelotophobic persons, individuals with gelotophobia felt weak at regulating their emotions, and the approaches they typically use to manage their emotions were considered inefficient by experts (Papousek et al, 2009;Weiss et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of patients in forensic settings are offenders who have committed violent crimes such as assaults, armed robberies, rape, manslaughter, or murder. Studies suggest that people with schizophrenia without a life-long history of antisocial behavior but who elicit violent behavior may demonstrate even more profound impairments in executive functions and working memory than people with schizophrenia without a history of violence (Barkataki et al, 2005;Fullam and Dolan, 2008;Reinharth et al, 2014;Soyka, 2011;Weiss, 2012). These impairments may limit the learning capacity of violent offenders and their ability to gain from an intense program of court-ordered competency restoration and psychiatric rehabilitation (Schwalbe and Medalia, 2007).…”
Section: Introductionmentioning
confidence: 99%